Subjective Well-Being by Gender - Joshi, Upasna (Journal of Economics and Behavioral Studies, 2010)
International competition and globalization of business and organizations, rapid technological change and higher customer demands for products and services with increasing emphasis on environmental issues change working life. Under these pressures in order to survive and make a positive result, companies must develop both their organization and people simultaneously with their products and technologies for improving the performance, work ability, commitment and well-being of employees. Therefore study of subjective well-being among male and female employees in IT industry is of paramount importance. Such study may affect the performance and over all well-being of not only employees but also of the organization as a whole. The study is descriptive in nature whereby an attempt is made to compare the level of subjective well-being among male and female employees in IT industry with the help of two questionnaires (Satisfaction with Life Scale and Positive Affectivity and Negative Affectivity Scale) and utilizing the survey technique. Subjective well-being is statistically analyzed by means, standard deviations, and t-ratio. The study shows that gender is not a determinant of subjective well-being, and both males and females perceive subjective well-being or evaluate their lives in a similar way. The level of life satisfaction among male and female IT employees is not comparable and there existed significant gender difference in the level of life satisfaction. The level of positive affectivity and negative affectivity among male and female IT employees was comparable and there exists no significant gender difference in the level of positive affectivity.